ESTIMASI NILAI MODULUS REAKSI TANAH DASAR (NILAI ‘k’) PADA MATERIAL TANAH LEMPUNG PENIRAMAN - Dian Sudiyono; Slamet Widodo; Eti Sulandari (JeLAST : Jurnal Teknik Kelautan , PWK , Sipil, dan Tambang, 2016)
Subgrade is a very important factor in the field of civil engineering, especially in designing the pavement, both rigid and flexible pavements pavement. According to some studies of land in West Kalimantan, especially land Peniraman have clay soil conditions that have small pebbles. Clay is technically more advantageous because it has a carrying capacity is high enough so that in designing the pavement is excellent for use as road subgrade. This research was carried out without disturbing the original soil conditions are then carried out by testing the physical properties and mechanical properties of the soil. Testing the physical properties of soil carried out by three methods: USCS, AASHTO, and the USDA. Based on the method USCS unknown land peniraman classified as ML (silt inorganic, fine sand once, powdered rock, fine sand clayed or argillaceous) and according to AASHTO classified land clayed with general levels most basic soil moderate to poor, while according to the USDA soil classified as loam or Clay. As for testing the mechanical properties of soil compaction test done and compressive strength test soil by CBR test and the test load plate to get the subgrade modulus value or the value of